Anti-corrosion primer for civil air defense door and preparation method thereof
By using phosphate-modified polysiloxane aqueous dispersion and neutral alkoxysilane crosslinking agent, the acid-base incompatibility problem of the bottom coating of air-raid shelter doors was solved, achieving a stable crosslinking network and independent conductive and anti-corrosion functions, thus improving the coating's construction adaptability and protective effect.
Patent Information
- Application Number
- CN202611283789.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-08-24
AI Technical Summary
In the prior art, when the base coating of the air defense door comes into contact with the acid-catalyzed hydrolysis solution and the subsequently added amine curing agent or alkaline component, there is a local acid-base shock, which affects the stability of the system and the density of the coating, and also has poor electrical conductivity.
A stable crosslinking network is formed by using phosphate-modified polysiloxane aqueous dispersion and neutral alkoxysilane crosslinking agent through interfacial grafting and independent functional design, avoiding acid-base reactions. The conductive and anti-corrosion functions are distributed to different carriers, which are realized by sheet-dot composite conductive fillers and fluorosilicone nanoparticles, respectively.
It improves the stability of the crosslinking system, maintains the independence of conductivity and corrosion protection functions, improves the adaptability of construction operations, and enhances the long-term protective capability of the coating.
Smart Images

Figure CN122810707B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional protective coatings, specifically to a conductive anti-corrosion primer material for air-raid shelter doors and its preparation method. Background Technology
[0002] Air defense doors, along with their frames, hinge seats, and embedded parts, are typically made of carbon steel or low-alloy steel. Their service environments may be characterized by humidity, salt deposition, dust friction, and static electricity buildup. In addition to providing adhesion and shielding against corrosion on the steel substrate, the base coat must also form a continuous but not overly conductive discharge path and maintain interlayer bonding with the subsequent topcoat. Waterborne polysiloxane systems possess potential for weather resistance and low volatile organic compounds; however, silane hydrolysis and condensation are typically significantly affected by pH. Acid-catalyzed hydrolysates are prone to localized acid-base shocks when in contact with alkaline waterborne dispersions, amine curing agents, or zinc salt pigments, leading to a sudden increase in system viscosity, gelation, or pigment flocculation.
[0003] To address the aforementioned issues, existing technologies attempt to enhance coating adhesion and corrosion resistance by modifying the resin with silane coupling agents or adding functional fillers. For example, Chinese invention patent CN107446116B discloses a method for synthesizing siloxane-modified epoxy resin and preparing its waterborne anti-corrosion coating. This method uses a siloxane hydrolysate obtained by acid-catalyzed hydrolysis of isopropanol, oxalic acid, and water, followed by reaction with epoxy resin. The primer uses graphene paste, zinc powder, and an epoxy curing agent. However, this approach belongs to an acid-catalyzed siloxane-epoxy / curing agent system. When the acid-catalyzed hydrolysate comes into contact with subsequently added amine curing agents or alkaline components, there is still a potential risk of localized acid-base shock, which may affect the system's stability and coating density.
[0004] In summary, how to achieve stable dispersion, metal anchoring, and crosslinking compatibility in a polysiloxane aqueous system without the aid of external emulsifiers and surface modifiers, and how to distribute conductive and anti-corrosion functions synergistically across different carriers, has become a pressing technical problem to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a conductive and anti-corrosion primer material for civil defense doors and its preparation method, so as to solve the technical problems such as acid-base incompatibility and poor conductivity stability of the primer crosslinking system in the prior art.
[0006] The specific technical solution is as follows: This invention provides a conductive and anti-corrosion primer for air-raid shelter doors, comprising separately packaged component A and component B. Component A, by wet basis weight, comprises: 30-40 parts of phosphate-modified polysiloxane aqueous dispersion, 22-26 parts of sheet-like conductor, 1-3 parts of dot-like conductor, 2-4 parts of zinc phosphate, 1-3 parts of zinc molybdate, 2-4 parts of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560), 0.5-1.5 parts of fumed silica, and 0.5-1.5 parts of tridecafluorooctyltriethoxysilane (FA). The composition comprises: 0.8-1.2 parts of S), 2-5 parts of tetraethyl orthosilicate (TEOS), 0.5-1.5 parts of polycarboxylate dispersant, 0.3-0.8 parts of polysiloxane defoamer, 0.3-0.8 parts of polyether-modified polysiloxane leveling agent, 0.2-0.8 parts of polyurethane associative thickener, and 6-10 parts of deionized water; the final pH value of component A is 5.8-6.5; component B is a neutral alkoxysilane crosslinking agent; the mass ratio of component A to component B is 100:(10-12).
[0007] Furthermore, the phosphate-modified polysiloxane aqueous dispersion comprises the following raw materials in parts by weight: 20-30 parts of hydroxyl-terminated polydimethylsiloxane (PDMS), 3-5 parts of KH-560, 1-2 parts of 85% phosphoric acid, and 8-12 parts of deionized water.
[0008] Furthermore, the sheet-like conductor is conductive mica powder; the dot-like conductor is antimony-doped tin oxide (ATO) conductive titanium dioxide; and the neutral alkoxysilane crosslinking agent is polyethyl silicate or TEOS.
[0009] This invention also provides a method for preparing a conductive and anti-corrosion primer for air-raid shelter doors, comprising the following steps: S1: Mix PDMS and KH-560, and heat the mixture under nitrogen protection. After cooling, add phosphoric acid dropwise and carry out the ring-opening reaction under heat preservation conditions. During the ring-opening reaction, take samples and monitor the intensity of the characteristic peak of the epoxy group in the sample using infrared spectroscopy. When the intensity of the characteristic peak of the epoxy group drops to less than 10% of the initial peak value, the ring-opening reaction is considered to have reached the endpoint. After the ring-opening reaction is completed, slowly add dilute ammonia water dropwise while continuously stirring and monitor the pH online. After adjusting the pH of the system, add deionized water and emulsify by high-speed shearing to obtain an aqueous dispersion of phosphate ester-modified polysiloxane for later use.
[0010] S2: Mix deionized water and polycarboxylate dispersant, then add zinc phosphate and zinc molybdate in sequence. Stir at low speed to fully wet the powder, then increase the stirring speed and disperse at medium speed. Subsequently, add flake conductive mica powder and spherical ATO conductive titanium dioxide powder, maintain the stirring speed and continue to disperse at medium speed to obtain a flake-dot composite conductive-corrosion inhibitor pre-dispersion slurry for later use.
[0011] S3: The pre-dispersed slurry of the sheet-dot composite conductive-corrosion inhibitor prepared in S2 is mixed with the aqueous dispersion of phosphate-modified polysiloxane prepared in S1. KH-560 is added and it is used to perform interfacial grafting with the flake conductive mica powder and the spherical antimony-doped tin oxide conductive titanium dioxide to obtain a mixed slurry. FAS and TEOS are mixed separately, and the pH is adjusted with glacial acetic acid and stirred for pre-hydrolysis to obtain a hydrolysate. The hydrolysate is mixed with the mixed slurry and then added with fumed silica, polysiloxane defoamer and polyether-modified polysiloxane leveling agent to generate fluorosilicone nanoparticles. After hydrolysis, the pH of the system is retested and adjusted with ammonia to maintain the pH value in the range of 5.8 to 6.5. Then, a polyurethane associative thickener is added to adjust the viscosity. The undispersed sheet-dot composite conductive-corrosion inhibitor agglomerates are removed by filtration to obtain component A.
[0012] S4: Polyethyl silicate is used as component B; component A and component B are mixed in a certain mass ratio and then cured to obtain a conductive and anti-corrosion primer.
[0013] Further, in S1, the reaction is carried out under nitrogen protection, which requires heating to 80~100℃ for 1~3 hours; after cooling, phosphoric acid is added dropwise, and the ring-opening reaction is carried out under heat preservation conditions, which requires cooling to 35~45℃ and heat preservation for 25~35 minutes; the pH of the system is adjusted to 6.0~6.5; the conditions for high-speed shear emulsification are set to a rotation speed of 3000~5000 rpm and a shearing time of 10~20 minutes.
[0014] Further, in S2, the low-speed stirring speed is set to 400~600 rpm, and the low-speed stirring time is set to 8~12 minutes; increasing the stirring speed and performing medium-speed dispersion specifically means increasing the speed to 800~1200 rpm and performing medium-speed dispersion for 15~25 minutes; maintaining the speed and continuing medium-speed dispersion for 25~35 minutes.
[0015] Further, in step S3, the stirring speed is set to 200~400 rpm; the pre-hydrolysis by adjusting the pH with glacial acetic acid and stirring specifically involves adjusting the pH value to the range of 4.5~5.0 and stirring at a temperature of 20~30℃ for 0.5~1.5 hours.
[0016] Furthermore, in step S4, the mass ratio of component A to component B is 100:(10~12); the maturation time is set to 8~12 minutes.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. Improve the stability of the crosslinking system: The present invention uses neutral polyethyl silicate or tetraethyl silicate as a crosslinking agent, which avoids the acid-base side reaction between phosphate groups and aminosilanes, so that the coating maintains the chemical activity of phosphate anchoring points while maintaining a high crosslinking density.
[0018] 2. Maintaining the independence of conductivity and corrosion protection functions: This invention maintains the sheet-dot composite conductive filler in an unmodified state to form a continuous conductive path, and introduces fluorosilicone nanoparticles as an independent hydrophobic functional layer, so that the conductivity and corrosion protection functions can be performed in parallel in the same coating without interfering with each other.
[0019] 3. Improved adaptability to construction operations: This invention uses phosphate ester-based polysiloxane aqueous dispersion as the film-forming material, which can be stably dispersed in the aqueous phase without the addition of external emulsifiers; the sheet-dot composite conductive filler is modified only by KH-560 in-situ interface modification, without the need to add a separate surface modifier; combined with room temperature moisture curing method and long pot life, the adaptability of the coating to different construction environments is improved.
[0020] 4. Enhanced long-term protective capability of coating: The affinity and adsorption of zinc salt particles by the phosphate ester side chain in this invention improves the dispersion stability of the corrosion inhibitor filler in the aqueous system. At the same time, the physical barrier effect of fluorosilicone nanoparticles delays the penetration path of corrosive media, which helps to extend the protective effect of the coating during its service life. Attached Figure Description
[0021] Figure 1 This is a flowchart of a conductive anti-corrosion primer material for air-raid shelter doors and its preparation method, according to the present invention.
[0022] Figure 2 The images show scanning electron microscope (SEM) and EDS elemental distribution maps of the coatings in the embodiments and comparative examples of the present invention; wherein, (a) is the cross-section of the coating of Example 1 (H1); (b), (c), and (d) are the surface filler dispersion morphology of the coatings of Example 1, Comparative Example 3 (C1), and Comparative Example 4 (C2), respectively; and (e) and (f) are the EDS elemental distribution maps of the cross-section of the coating formed by the coating prepared in Example 1.
[0023] Figure 3 The images show the atomic force microscopy (AFM) morphology and C-AFM local conductivity test spectra of the coatings formed by the coatings prepared in Example 1 and Comparative Example 3 of this invention. Detailed Implementation
[0024] The present invention can be better understood from the following embodiments. However, those skilled in the art will readily understand that the descriptions in the embodiments are for illustrative purposes only.
[0025] This invention proposes a conductive anti-corrosion primer material for air-raid shelter doors and its preparation method, such as... Figure 1The diagram shown is a flowchart of a conductive anti-corrosion primer material for air-raid shelter doors and its preparation method according to the present invention. The detailed preparation steps are as follows: S1. Resin Synthesis Hydroxyl-terminated polydimethylsiloxane (PDMS) and γ-glycidoxypropyltrimethoxysilane (KH-560) were reacted under nitrogen protection at elevated temperature. The methoxysilane group in the KH-560 molecule underwent a de-alcoholization condensation reaction with the terminal hydroxyl groups of PDMS, and the side chains containing epoxy groups were branched to the polysiloxane backbone via Si-O-Si bonds. After cooling, phosphoric acid was added dropwise and the reaction was maintained at this temperature. Utilizing the acidic ring-opening epoxy groups of phosphoric acid, mono- or diester structures of phosphate were generated, thereby introducing hydrophilic polar phosphate groups onto the hydrophobic polysiloxane side chains. These polar phosphate groups are ionizable in the aqueous phase, allowing the polymer segments to self-stable disperse in water without the addition of external emulsifiers, forming an aqueous dispersion. Simultaneously, these polar phosphate groups can form stable interfacial bonds with the substrate surface during subsequent coating, enhancing the interfacial adhesion of the coating. During the heat-maintaining reaction, the degree of disappearance of the characteristic absorption peaks of the epoxy groups was monitored in real time using infrared spectroscopy to determine the endpoint of the ring-opening reaction. After the ring-opening reaction is completed, the pH of the system is adjusted to 6.0-6.5 with ammonia to neutralize the acidity of the residual free phosphoric acid and some of the phosphate esters, so as to avoid the strong acid environment from corroding the subsequently added corrosion inhibitor filler. At the same time, deionized water is added and emulsified by high-speed shearing to obtain a phosphate ester-modified polysiloxane aqueous dispersion. The aqueous dispersion system is stable in a pH range suitable for storage and subsequent preparation.
[0026] S2. Packer predispersion Zinc phosphate and zinc molybdate were sequentially added to the aqueous phase containing a dispersant. Low-speed wetting and medium-speed dispersion were used to fully deagglomerate the zinc salt particles and uniformly suspend them in the medium. Subsequently, flake-shaped conductive mica powder and spherical antimony-doped tin oxide (ATO) conductive titanium dioxide were added, and dispersion continued at a medium speed. Utilizing the anchoring effect and steric hindrance of the dispersant, the flake-shaped conductive mica powder and spherical antimony-doped tin oxide (ATO) conductive titanium dioxide were uniformly dispersed and formed a pre-conductive network of inter-layer contact, resulting in a flake-point composite conductive filler. The flake-shaped conductive mica has a large aspect ratio, enabling it to form a continuous conductive backbone with surface-to-surface contact in the coating. The spherical ATO conductive titanium dioxide fills the gaps between the flakes, acting as point bridges where the flake-shaped conductive mica powder is poorly oriented or partially discontinuous, thus reducing the overall percolation threshold. During dispersion, the material temperature must be controlled to not exceed 45℃ to avoid localized overheating caused by mechanical dispersion, which could lead to dispersant desorption or changes in the surface properties of the filler. After dispersion, the flake-point composite conductive-corrosion-inhibiting filler pre-dispersion slurry is obtained.
[0027] S3.A Component Preparation The pre-dispersed slurry of the sheet-dot composite conductive-corrosion inhibitor was transferred to a reactor. After adding the phosphate-modified polysiloxane aqueous dispersion, KH-560 was added first, and the mixture was stirred to ensure full contact and reaction with the sheet-dot composite conductive filler obtained in step S2. The methoxysilane end of the KH-560 molecule undergoes a condensation reaction with the hydroxyl groups on the surface of the sheet-dot composite conductive filler, grafting onto the filler surface through Si-O-Si bonds, thus improving the interfacial compatibility between the sheet-dot composite conductive filler and the polysiloxane, completing the interfacial grafting. Subsequently, tridecafluorooctyltriethoxysilane (FAS) and tetraethyl orthosilicate (TEOS) were added, and the pH of the system was adjusted to 4.5–5.0 with glacial acetic acid. Under these acidic conditions, the alkoxy groups of FAS and TEOS hydrolyzed to generate silanol groups; these silanol groups underwent a condensation reaction to remove water molecules, and multiple molecules were linked together through Si-O-Si bonds, agglomerating to form fluorosilicone hybrid nanoparticles. TEOS provides the rigid framework and dense filling effect of the particles, while the fluorocarbon segments of FAS endow the particles with low surface energy properties. Since the surface of the sheet-point composite conductive filler is pre-occupied by KH-560, the fluorosilicone hybrid nanoparticles form independently in the liquid phase and do not cover the surface of the sheet-point composite conductive filler. The fumed silica added to the system is a hydrophilic nanoparticle, mainly acting as a thixotropic thickener. After hydrolysis, the pH is adjusted to 5.8-6.5 with ammonia, and a thickener is added to adjust the viscosity. Filtering yields component A.
[0028] S4.B component mixed curing Polyethyl silicate (component B) is used as a crosslinking agent, mixed with component A at a specific mass ratio, and cured to obtain a conductive and anti-corrosion primer. Polyethyl silicate is a neutral alkoxysilane oligomer containing multiple hydrolyzable silanyl ethoxy groups (-Si-OC2H5) in its molecular structure. Under humid conditions, it hydrolyzes to generate silanol groups, which condense with the silanol groups remaining on the surface of the fluorosilicone nanoparticles in component A, forming a three-dimensional Si-O-Si crosslinked network, thus achieving room temperature curing of the coating. This crosslinking agent does not contain amino or other basic groups and does not react with the phosphate groups, therefore it does not produce ammonium salt precipitation, does not disrupt the filler dispersion, and does not consume phosphate anchoring points. The byproduct released during crosslinking is ethanol, which does not introduce corrosive ions. After coating, the coating gradually cures in a humid environment at room temperature. Simultaneously, the phosphate groups migrate to the substrate interface and form interfacial bonds with the substrate surface, achieving simultaneous crosslinking of the coating bulk and interfacial anchoring.
[0029] This invention includes the following key points: 1. Construction of neutral crosslinking system Traditional phosphate ester-based polysiloxane conductive anticorrosive coatings use aminosilane crosslinking agents. The acidic groups of phosphate ester and the basic groups of aminosilane are prone to acid-base neutralization during preparation and storage, generating ammonium salt precipitates, which damage the dispersion system, block the crosslinking reaction and consume the anchoring points of phosphate ester, resulting in decreased adhesion, shortened pot life and deterioration of anticorrosive performance.
[0030] This invention uses polyethyl or tetraethyl orthosilicate as a crosslinking agent to replace aminosilane. Polyethyl or tetraethyl orthosilicate are neutral alkoxysilane compounds whose molecular structure does not contain amino or other basic groups, and therefore does not undergo acid-base reactions with phosphate groups. The alkoxysilane in the crosslinking agent undergoes hydrolysis under the influence of moisture in component A and ambient humidity, and condenses with silanol or hydroxyl groups in the system to form a crosslinked structure dominated by Si-O-Si bonds. This crosslinking process does not involve ionic intermediates, does not produce salt byproducts, and does not consume the active groups of the phosphate ester side chains, thus ensuring that the phosphate ester groups retain their chemical activity for interfacial bonding with the metal substrate. Simultaneously, the byproduct released by the crosslinking reaction is ethanol, avoiding the adverse effects of small molecule salt residues on the anti-corrosion performance of the coating. Through the reconstruction of the above crosslinking system, this invention effectively avoids the performance degradation problems caused by acid-base side reactions in the prior art while maintaining the crosslinking density of the coating.
[0031] 2. Decoupling design of conductive and hydrophobic functions Existing technologies often use fluorosilanes to modify conductive fillers to achieve both conductivity and hydrophobicity. However, the fluorocarbon chains form an insulating coating layer on the filler surface, increasing the particle contact resistance and raising the surface resistivity. This requires increasing the amount of filler to meet the standards, resulting in decreased coating density and increased costs.
[0032] This invention assigns conductive and hydrophobic functions to different material carriers, achieving independent control of both in the coating. The conductive function is provided by a sheet-dot composite conductive network composed of flake-shaped conductive mica powder and spherical ATO conductive titanium dioxide, forming a sheet-dot composite conductive filler. The spherical antimony-doped tin oxide conductive titanium dioxide is not pre-treated with fluorinated silanes for hydrophobic coating. During the formulation of component A, KH-560 can undergo interfacial grafting with the surface of the sheet-dot composite conductive filler to improve compatibility. However, the fluorinated siloxane condensate in the system is controlled to not form a continuous insulating coating layer on the surface of the sheet-dot composite conductive filler, allowing conductive pathways to still be formed in the particle contact area, maintaining unobstructed electron transport channels. The hydrophobic function is achieved as an independent functional phase by fluorosilicone nanoparticles generated from the co-hydrolysis of tridecafluorooctyltriethoxysilane (FAS) and tetraethyl orthosilicate (TEOS). The fluorosilicone nanoparticles, with a Si-O-Si network formed by TEOS condensation as the framework, are uniformly dispersed in the continuous polysiloxane phase. The fluorocarbon segments provided by FAS reduce the surface energy of the coating, and their content is controlled within a range that makes it difficult to form a continuous insulating film. Through the above functional decoupling design, the dot-shaped conductive filler remains unmodified to form a continuous conductive path, while the fluorosilicone nanoparticles independently provide hydrophobic and densification functions. The two functions can be performed in parallel in the same coating without interfering with each other.
[0033] To verify the interfacial bonding state of the coating, the dispersion morphology of the sheet-dot composite conductive filler, and the spatial distribution of fluorosilicone nanoparticles in this invention, the coatings obtained in Example 1 and Comparative Examples 3 and 4 were characterized by SEM-EDS. Figure 2 As shown, Figure 2 (a) is a SEM image of the cross-section of the coating formed by the coating prepared in Example 1, showing that the coating is tightly bonded to the steel substrate interface, the coating cross-section is dense, and there are no obvious micropores or cracks. Figure 2 (b) Figure 2 (c) Figure 2 (d) in the figures are the surface filler dispersion morphology diagrams of the coatings formed by the coatings prepared in Example 1, Comparative Example 3, and Comparative Example 4, respectively. In Example 1, the sheet-like conductive mica and the spherical ATO conductive titanium dioxide are uniformly dispersed, and the two together form a "sheet-dot" composite conductive network. In Comparative Example 3, only the sheet-like mica is isolated and there is a lack of dot-like bridging between the sheets. In Comparative Example 4, only the spherical ATO conductive titanium dioxide is dispersed, and it is difficult to form a long-range continuous conductive path. Figure 2 (e) Figure 2 In Figure (f), the cross-sectional EDS elemental surface scan spectrum of the coating in Example 1 shows that the fluorine signal is mainly distributed in the matrix region rather than enriched on the surface of the sheet-dot composite conductive filler. This indicates that the fluorine-silicon nanoparticles are dispersed as independent functional phases in the coating and do not form a continuous insulating coating on the surface of the sheet-dot composite conductive filler. The aforementioned matrix region refers to the continuous phase in the coating excluding the sheet-dot composite conductive filler.
[0034] To further verify whether the surface of the sheet-dot composite conductive filler can still maintain conductive pathways, the coatings formed by the coatings prepared in Example 1 and Comparative Example 3 were characterized by AFM and C-AFM. Figure 3 As shown, Figure 3 The top row shows the AFM morphology of the coating, and the bottom row shows the C-AFM local conductivity test spectrum of the corresponding area. The stronger the current signal, the better the conductivity of the area. In the C-AFM spectrum of Example 1, the current signal is mainly concentrated in the area where the sheet-point composite conductive filler is located, indicating that a continuous insulating layer has not been formed on the surface of the filler, and the particle contact area can still maintain a conductive path. In Comparative Example 3, due to the lack of point-shaped conductive bridging, the current signal between the sheets is discontinuous, and the connectivity of the conductive network decreases.
[0035] Example 1 A method for preparing a conductive anti-corrosion primer for air-raid shelter doors, using raw materials as shown in Table 1, includes the following steps: Table 1 Raw Material Information Table
[0036] S1: Add 25 parts PDMS and 4 parts KH-560 to the reactor, heat to 90℃ under nitrogen protection and react for 2 hours; then cool to 40℃, add 1.5 parts 85% phosphoric acid dropwise, keep the reaction at this temperature for 30 minutes, take samples every 10 minutes during the reaction and monitor the intensity of the characteristic peak of the epoxy group in the sample using infrared spectroscopy. When the intensity of the characteristic peak of the epoxy group drops to less than 10% of the initial peak value, the ring-opening reaction is determined to have reached the endpoint; after the reaction is kept at this temperature, slowly add dilute ammonia water dropwise under continuous stirring for no less than 30 minutes and monitor the pH online, adjust the pH value of the system to 6.3, add 10 parts deionized water, and shear at 4000 rpm for 15 minutes using a high-speed shear emulsifier to obtain the phosphate ester-modified polysiloxane aqueous dispersion, and seal and refrigerate at 4℃ for later use.
[0037] S2: Add 8 parts deionized water and 1 part polycarboxylate dispersant to the dispersion tank, start the high-speed disperser and stir at a low speed of 500 rpm, add 3 parts zinc phosphate and 2 parts zinc molybdate in sequence, stir at low speed for 10 minutes and make the powder fully wet, then increase the speed to 1000 rpm and disperse at medium speed for 20 minutes; then add 24 parts flake conductive mica powder and 2 parts spherical ATO conductive titanium dioxide, maintain the speed and continue to disperse at medium speed for 30 minutes, control the material temperature not to exceed 45℃ during the dispersion process, and obtain the flake-dot composite conductive-corrosion inhibitor pre-dispersion slurry for later use.
[0038] S3: Transfer the pre-dispersion slurry of the sheet-dot composite conductive-corrosion inhibitor prepared in S2 to the reactor, start stirring and stir at a low speed of 300 rpm, add 40 parts of the phosphate ester-modified polysiloxane aqueous dispersion prepared in S1 and 3 parts of KH-560, and stir to ensure full contact with the sheet-like conductive mica powder and the spherical ATO conductive titanium dioxide powder; separately take 1 part of FAS, 3 parts of TEOS, 1 part of fumed silica, 0.5 parts of polysiloxane defoamer and 0.5 parts of polyether-modified polysiloxane leveling agent, and add glacial acetic acid conditioning agent dropwise. The pH was adjusted to 4.8, and the mixture was stirred at 25°C for 1 hour to allow FAS and TEOS to hydrolyze in situ to generate fluorosilicone nanoparticles, thus preparing a low-fluorine nanosiloxane hydrolysate. This low-fluorine nanosiloxane hydrolysate was slowly added to a reaction vessel, while maintaining the pH of the system at 5.8-6.5 with ammonia water to ensure that the pre-hydrolyzed fluorosilicone nanoparticles were uniformly dispersed in the system. Subsequently, 0.5 parts of polyurethane associative thickener were added to adjust the viscosity. The mixture was then filtered through a 200-mesh sieve to remove the insufficiently dispersed sheet-dot composite conductive-corrosion inhibitor agglomerates, yielding component A.
[0039] S4: Take 10 parts of polyethyl silicate as component B; mix component A and component B at a mass ratio of 100:11, mature for 10 minutes, and the pot life after mixing is 4~6 hours, thus obtaining the electrostatic anti-corrosion primer material.
[0040] Example 2 The preparation method is the same as in Example 1, except that: S1: 20 parts PDMS and 3 parts KH-560; 1 part 85% phosphoric acid; 8 parts deionized water; S2: 6 parts deionized water and 0.5 parts polycarboxylate dispersant; 2 parts zinc phosphate and 1 part zinc molybdate; 22 parts flake conductive mica powder and 1 part spherical ATO conductive titanium dioxide; S3: 30 parts of phosphate ester-modified polysiloxane aqueous dispersion; 0.8 parts of FAS, 2 parts of TEOS, 2 parts of KH-560, 0.5 parts of fumed silica, 0.3 parts of defoamer and 0.3 parts of leveling agent; 0.2 parts of polyurethane associative thickener; All other steps are the same.
[0041] Example 3 The preparation method is the same as in Example 1, except that: S1: 30 parts PDMS and 5 parts KH-560; 2 parts 85% phosphoric acid; 12 parts deionized water; S2: 10 parts deionized water and 1.5 parts polycarboxylate dispersant; 4 parts zinc phosphate and 3 parts zinc molybdate; 26 parts flake conductive mica powder and 3 parts spherical ATO conductive titanium dioxide; S3: 40 parts of phosphate ester-modified polysiloxane aqueous dispersion; 1.2 parts of FAS, 5 parts of TEOS, 4 parts of KH-560, 1.5 parts of fumed silica, 0.8 parts of defoamer and 0.8 parts of leveling agent; 0.8 parts of polyurethane associative thickener; All other steps are the same.
[0042] Example 4 The preparation method is the same as in Example 1, except that: S1: Heat to 80℃ and react for 1 hour; cool to 35℃; maintain the temperature for 25 minutes; adjust the pH of the system to 6.0; shear at 3000 rpm for 10 minutes; S2: Stir at a low speed of 400 rpm for 8 minutes; increase to a medium speed of 800 rpm and disperse for 15 minutes; continue to disperse at a medium speed for 25 minutes. S3: Stir at a low speed of 200 rpm; adjust the pH of the system to 4.5, and stir at 20°C for 0.5 hours; S4: Mix component A and component B at a mass ratio of 100:12 and cook for 8 minutes. All other steps are the same.
[0043] Example 5 The preparation method is the same as in Example 1, except that: S1: Heat to 100℃ and react for 3 hours; cool to 45℃; maintain the temperature for 35 minutes; adjust the pH of the system to 6.5; shear at 5000 rpm for 20 minutes; S2: Stir at 600 rpm at low speed for 12 minutes; increase to 1200 rpm at medium speed and disperse for 25 minutes; continue to disperse at medium speed for 35 minutes. S3: Stir at a low speed of 400 rpm; adjust the pH of the system to 5.0, and stir at 30°C for 1.5 hours; S4: Mix component A and component B at a mass ratio of 100:10 and cook for 12 minutes. All other steps are the same.
[0044] Example 6 The preparation method is the same as in Example 1, except that: S4: Replace polyethyl silicate with tetraethyl orthosilicate (TEOS), both of which are neutral alkoxysilane crosslinking agents; All other steps are the same.
[0045] Comparative Example 1 The traditional process is used to prepare an anti-static and anti-corrosion primer material. The preparation method is as follows: Take 100 parts of epoxy resin, 20-30 parts of conductive mica powder, 10-30 parts of xylene, 1-3 parts of dispersant, and 0.3-1 parts of defoamer. Put them into a dispersion tank according to the ratio and disperse at a high speed of 1000-2000 rpm for 30-60 minutes. If necessary, grind them with a sand mill until the fineness is ≤50μm to obtain the main agent of the coating. Before construction, mix the isocyanate curing agent according to the resin system at a ratio of 100:(5-20) to obtain the anti-static and anti-corrosion primer coating.
[0046] Comparative Example 2 The preparation method is the same as in Example 1, except that: S1: The step of adding phosphate-modified polysiloxane aqueous dispersion is omitted and replaced with nonionic emulsified hydroxyl-terminated polydimethylsiloxane dispersion, which is emulsified with fatty alcohol polyoxyethylene ether at 2.0% of polymer solids, pH 7.0, and does not contain phosphate groups; All other steps are the same.
[0047] Comparative Example 3 The preparation method is the same as in Example 1, except that: S2: Omit the step of adding spherical ATO conductive titanium dioxide, and adjust the amount of flake conductive mica powder to 26 parts; All other steps are the same.
[0048] Comparative Example 4 The preparation method is the same as in Example 1, except that: S2: Omit the step of adding flake conductive mica powder, and adjust the amount of spherical ATO conductive titanium dioxide to 26 parts; All other steps are the same.
[0049] Comparative Example 5 The preparation method is the same as in Example 1, except that: S3: Omit the steps of adding FAS and TEOS, and make up the difference with 4 parts of deionized water; All other steps are the same.
[0050] Comparative Example 6 The preparation method is the same as in Example 1, except that: S4: Omit the step of adding polyethyl silicate and replace it with acidic polyethyl silicate pre-hydrolyzed by oxalic acid-water-ethanol, with an acid value of 8.0 mg KOH / g and a pH of 2.8 for the 10% water-ethanol hydrolysate; All other steps are the same.
[0051] Experimental Example 1 The conductive anti-corrosion primers prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested: 1) Surface resistivity: Referring to GB / T 16906-1997 "Method for Determination of Resistivity of Conductive Coatings for Petroleum Tanks", take one clean polyester film with an area of 150mm×150mm and another with an area of 140mm×140mm. Cover the center of the larger film with the smaller film and fix the edges with cellophane tape to form a double-layer substrate with overlapping edges. Immerse the substrate vertically into the coating at a uniform speed, leave it for 10 seconds, remove it, and let it air dry to allow the solvent to evaporate. Then, invert the substrate 180° and immerse it a second time. After removal, cure it completely under standard environmental conditions. Cut the prepared dry film and polyester film substrate together into strips of 40mm×130mm. Prepare at least six strips for each sample, and select three of them for testing. Place parallel electrodes on the surface of the sample, apply a DC voltage, and measure the current generated between the electrodes. Each group of valid samples should have no less than 3 samples, and the final result is the average.
[0052] 2) Adhesion: Refer to GB / T 5210-2006 "Paints and Varnishes - Pull-off Adhesion Test". Use a 120mm×50mm×(1.5~3)mm steel plate. Apply the coating to the surface of the steel plate according to the actual construction method, control the dry film thickness, and after complete curing, stick the test column coated with adhesive to the coating surface. After the adhesive cures, cut through the test column to the substrate and remove the excess coating to obtain the test sample. Place the test sample on the tensile testing machine, carefully center the test column, and make the tensile force evenly applied to the test area. Apply tensile stress in the direction perpendicular to the plane of the painted substrate. The stress increases steadily at a rate not exceeding 1MPa / s. The failure of the test combination should be completed within 90s from the application of stress. Record the tensile force value of the failure test combination. The nature of the damage is determined by visual inspection of the damaged surface. The type of damage is evaluated according to the standard (cohesive failure of substrate A, adhesion failure between coating A / B and substrate, cohesive failure of coating B, etc.), and the area percentage of each type of damage is estimated. The adhesion strength is expressed as the failure strength σ = F / A (unit MPa), where F is the destructive force (unit N) and A is the area of the test column (unit mm). 2 Each group should have no fewer than 3 valid samples, and the final result should be the average.
[0053] Experimental Example 2 The conductive and anti-corrosion primers prepared in Examples 1-6 and Comparative Examples 1-6 were subjected to a 1000-hour salt spray test. Referring to GB / T 1771-2007 "Paints and Varnishes - Determination of Resistance to Neutral Salt Spray", the coating was sprayed onto a 150mm×100mm×(0.8~1.5)mm steel plate with a dry film thickness of 65~80μm. After curing under standard conditions, the edges were sealed with the same type of coating. A scratch of about 50mm in length, penetrating to the substrate (≥20mm from the edge) was made on the plate surface with a hard scribe line to obtain the sample. The sample was placed in a salt spray test chamber, and a neutral salt spray was formed by spraying a sodium chloride solution with a mass concentration of (50±5)g / L. The spray collection rate was controlled at 1~2.5mL / h, and the pH value of the collected solution was maintained between 6.5 and 7.2. The test plate was continuously exposed in the test chamber at 35±2℃ for 1000h.
[0054] After the predetermined period is reached, the samples are taken out and evaluated in accordance with the provisions of HG / T 4569-2013 "Conductive Coatings for Petroleum and Petroleum Product Storage and Transportation Equipment". Specifically, the evaluation includes: (1) Determining the surface resistivity of the coating after the salt spray test in accordance with GB / T 16906-1997 "Method for Determining the Resistivity of Conductive Coatings for Petroleum Tanks". Each group has no less than 3 valid samples, and the arithmetic mean is taken; (2) Observing whether there are blistering, rust, peeling and other damage phenomena on the surface of the test plate and rating them; (3) Measuring the width of rust spread on one side of the scratch. The salt spray resistance of the coating is evaluated by comprehensively considering the above three indicators.
[0055] Experimental Example 3 After preparing coatings according to the method of Experimental Example 2, the coatings of Examples 1, 3, and 4 were subjected to microscopic morphology observation and elemental distribution characterization: 1) Coating test block cutting: A low-speed diamond cutter is used to cut along the direction perpendicular to the coating / steel substrate interface to obtain a coating test block with a size of about 8mm×8mm. The temperature of the cutting fluid is controlled to be below 30℃ throughout the process to avoid thermal damage to the coating resin caused by high temperature.
[0056] 2) Fluorine-free cold embedding: Select low-viscosity cold embedding epoxy resin without fluorine to embed the test block; after the resin and curing agent are fully mixed, vacuum degassing is performed, and the mixture is slowly injected into the mold. The test block is kept vertical and fully cured at room temperature before demolding.
[0057] 3) Gradual wet sanding: Use 800 grit, 1200 grit, 2000 grit and 4000 grit SiC waterproof sandpaper to wet grind in stages. Rotate the sample 90° for each grit change until the scratches from the previous grinding stage are completely eliminated, ensuring a flat and uniform cross-section.
[0058] 4) Diamond fine polishing and argon ion final polishing: The sample was mechanically polished with 3μm and 1μm diamond suspensions to eliminate the fine scratches of the sandpaper; then it was treated with wide beam argon ion polishing: polished for 30 minutes at 5kV and 5° incident angle, and finally cleaned with 2kV low energy beam for 10 minutes to obtain a smooth and realistic coating cross section.
[0059] 5) Differentiated vapor deposition treatment of test samples: A 5-8 nm carbon conductive film is vapor deposited on the surface of the coated sample.
[0060] 6) Parameter settings: Set the accelerating voltage to 5kV and the working distance to 5~8mm; the energy dispersive spectrometer adopts the area distribution scanning mode, and the single area scan acquisition time is not less than 120s.
[0061] The performance test results and salt spray test results of Examples 1 to 6 and Comparative Examples 1 to 6 are shown in Table 2 and Table 3, respectively.
[0062] Table 2. Performance Measurement Comparison Table of Examples 1-6 and Comparative Examples 1-6
[0063] Table 3. Comparison of salt spray test results for Examples 1-6 and Comparative Examples 1-6
[0064] As shown in Tables 2 and 3, the surface resistivity of the conductive and anti-corrosion primer material prepared in Example 1 of this invention is 3.42 × 10⁻⁶. 7 The surface resistivity is 3.86 × 10⁻⁶ Ω, with an adhesion of 9.38 MPa. After 1000 hours of neutral salt spray testing, the surface resistivity is 3.86 × 10⁻⁶. 8 The corrosion spread width at the scratch was 1.2 mm, and no blistering, rust, cracking, or peeling was observed in the unscratched area. These results indicate that the interfacial bonding provided by the phosphate groups and the physical barrier effect of the fluorosilicone nanoparticles work synergistically to enable the coating to maintain its electrostatic conductivity while also providing long-term corrosion protection.
[0065] Example 2 shows that reducing the amount of resin and crosslinking agent resulted in the most significant decrease in adhesion due to insufficient crosslinking density, indicating that the resin content and the amount of KH-560 directly affect the cohesive strength of the coating; after salt spray, the resistivity increased to 6.25 × 10⁻⁶. 8 The corrosion spread width at the scratch was 1.8 mm, which proves that the corrosive medium can penetrate more easily when the cross-linking is insufficient, and the stability of the conductive network is damaged.
[0066] Example 3 increased the dosage of each component to the maximum limit, increasing the crosslinking density and anchoring points, resulting in an adhesion strength of 10.82 MPa and a resistivity of only 2.41 × 10⁻⁶ after salt spraying. 8The corrosion spread width at the scratch was only 0.9 mm, indicating that the dense cross-linked network and sufficient interfacial bonding can effectively inhibit the penetration of corrosive media and protect the interface of the sheet-point composite conductive filler from corrosion damage.
[0067] In Example 4, reducing the reaction temperature and time resulted in a decrease in adhesion to 8.42 MPa. This was because insufficient reaction temperature and time led to incomplete phosphate esterification and a low grafting rate of phosphate ester groups. Additionally, insufficient dispersion speed caused filler agglomeration and increased interface defects.
[0068] In Example 5, increasing the reaction temperature and time significantly improved all performance characteristics compared to Example 4, indicating that increasing the reaction temperature and time promoted the complete phosphoesterification reaction and increasing the dispersion speed improved the uniformity of the filler dispersion. However, the overall performance was still slightly lower than that of Example 1, indicating that the parameters of Example 1 were close to the optimal range, and excessive enhancement had limited contribution to performance improvement.
[0069] In Example 6, after replacing the crosslinking agent with TEOS, the surface resistivity was 3.95 × 10⁻⁶. 7 The adhesion strength was 8.67 MPa, which is basically the same as that in Example 1, indicating that both TEOS and polyethyl silicate can effectively construct a cross-linked network. Both are neutral alkoxysilane cross-linking agents and can be used interchangeably according to actual needs.
[0070] Comparative Examples 1 to 6, lacking key technologies, showed varying degrees of reduced overall performance compared to the examples. Comparative Example 1, using a physical mixture of traditional epoxy resin and flake-shaped conductive mica powder, did not contain phosphate ester-based polysiloxane and therefore lacked the chemical anchoring ability provided by phosphate ester groups, resulting in an adhesion strength of only 6.85 MPa, far lower than that of the examples. Furthermore, the epoxy system lacked sufficient hydrophobicity, leading to a resistivity increase to 18.51 × 10⁻⁶ after salt spray testing. 8 The corrosion spread width at the scratch was 4.8 mm, and the unscratched area showed grade 2 blistering and rust, indicating that the chemical anchoring of phosphate ester and the hydrophobic barrier of polysiloxane are crucial to adhesion and salt spray resistance.
[0071] Comparative Example 2 used a polysiloxane dispersion without phosphate ester side chains, and the adhesion dropped significantly to 5.24 MPa. At the same time, the dispersion stability of the corrosion inhibitor filler in the system deteriorated, indicating that phosphate ester groups play an important role in improving adhesion and stabilizing the dispersion of fillers.
[0072] Comparative Example 3 did not include spherical ATO conductive titanium dioxide; the conductive pathways were constructed solely by flake-like conductive mica powder. Lacking point-like bridging between the flakes, the initial resistivity increased to 26.17 × 10⁻⁶. 7 Ω, further increased to 30.24 × 10 after salt spray. 8 Ω demonstrates that point conductors play an important role in reducing initial resistivity and maintaining the stability of conductive networks under salt spray conditions.
[0073] Comparative Example 4 did not include flake-shaped conductive mica powder; the conductive pathway was constructed solely by spherical ATO conductive titanium dioxide. The particles maintained point-to-point contact, resulting in limited contact sites and high contact resistance, making it difficult to form a long-range continuous conductive network. The initial resistivity was as high as 379.56 × 10⁻⁶. 7 Ω, increased to 425.18×10 after salt spray. 8 Ω, the corrosion spread width at the scratch is 5.2mm, and the unscratched area shows level 3 blistering, rusting and peeling, proving that the sheet conductor is the basic framework for building an efficient conductive network.
[0074] Comparative Example 5, lacking FAS and TEOS and fluorosilicone nanoparticles, retained phosphate groups and a sheet-dot composite conductive network, exhibiting good initial conductivity. However, its resistivity increased to 4.65 × 10⁻⁶ after salt spraying. 8 The corrosion spread width at the scratch was 2.1 mm, indicating that the densification of fluorosilicone nanoparticles and the hydrophobic barrier of fluorocarbon chains make important contributions to the stability of the conductive network under salt spray environment.
[0075] Comparative Example 6 used acidic polyethyl silicate pre-hydrolyzed with oxalic acid instead of neutral polyethyl silicate. Under acidic conditions, the phosphate groups underwent an ion exchange reaction with the corrosion-inhibiting filler, disrupting the dispersion system and corroding the metal interface. The adhesion was severely reduced to 4.76 MPa, and the resistivity after salt spray increased to 27.58 × 10⁻⁶. 8 The corrosion spread width at the scratch was 6.5 mm, and the unscratched area showed grade 3 blistering and peeling, proving that the acidity or alkalinity of the crosslinking agent has a decisive influence on the system's compatibility and anti-corrosion performance.
[0076] In summary, this invention integrates the "three functions in one material" of a phosphate ester-based polysiloxane aqueous dispersion, simultaneously achieving self-emulsifying dispersion, substrate interface bonding, and corrosion-inhibiting filler affinity and stability. The construction of a sheet-dot composite conductive network enhances conductivity uniformity and construction tolerance. The introduction of fluorosilicone nanoparticles decouples conductivity and hydrophobic corrosion protection. The synergistic effect of these functional components results in a coating that possesses excellent electrostatic conductivity, high adhesion, and long-lasting corrosion protection.
Claims
1. A conductive and anti-corrosion primer material for air-raid shelter doors, characterized in that, The product comprises separately packaged components A and B. Component A, by wet weight, includes: 30-40 parts of phosphate-modified polysiloxane aqueous dispersion, 22-26 parts of sheet-like conductor, 1-3 parts of dot-like conductor, 2-4 parts of zinc phosphate, 1-3 parts of zinc molybdate, 2-4 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 0.5-1.5 parts of fumed silica, 0.8-1.2 parts of tridecafluorooctyltriethoxysilane, and orthosilicic acid. The composition comprises 2-5 parts ethyl acetate, 0.5-1.5 parts polycarboxylate dispersant, 0.3-0.8 parts polysiloxane defoamer, 0.3-0.8 parts polyether-modified polysiloxane leveling agent, 0.2-0.8 parts polyurethane associative thickener, and 6-10 parts deionized water; the final pH value of component A is 5.8-6.5; component B is a neutral alkoxysilane crosslinking agent; the mass ratio of component A to component B is 100:(10-12). The phosphate-modified polysiloxane aqueous dispersion comprises the following raw materials in parts by weight: 20-30 parts of hydroxyl-terminated polydimethylsiloxane, 3-5 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 1-2 parts of 85% phosphoric acid, and 8-12 parts of deionized water. The sheet-like conductor is sheet-like conductive mica powder; the dot-like conductor is spherical antimony-doped tin oxide conductive titanium dioxide; the neutral alkoxysilane crosslinking agent is polyethyl silicate or tetraethyl orthosilicate.
2. A method for preparing a conductive anti-corrosion primer material for air-raid shelter doors as described in claim 1, characterized in that, Includes the following steps: S1: Hydroxyl-terminated polydimethylsiloxane and γ-glycidyl etheroxypropyltrimethoxysilane were mixed and reacted under nitrogen protection. After cooling, phosphoric acid was added dropwise, and a ring-opening reaction was carried out under heat preservation conditions. During the ring-opening reaction, samples were taken and the intensity of the characteristic peak of the epoxy group in the sample was monitored by infrared spectroscopy. When the intensity of the characteristic peak of the epoxy group dropped to less than 10% of the initial peak value, the ring-opening reaction was determined to have reached the endpoint. After the ring-opening reaction was completed, dilute ammonia was slowly added dropwise under continuous stirring and the pH was monitored online. After adjusting the pH of the system, deionized water was added, and the mixture was emulsified by high-speed shearing to obtain an aqueous dispersion of phosphate ester-modified polysiloxane for later use. S2: Mix deionized water and polycarboxylate dispersant, add zinc phosphate and zinc molybdate in sequence, stir at low speed to fully wet the powder, then increase the stirring speed and disperse at medium speed; then add flake conductive mica powder and spherical antimony-doped tin oxide conductive titanium dioxide, maintain the speed and continue to disperse at medium speed to obtain flake-dot composite conductive-corrosion inhibitor filler pre-dispersion slurry for later use; S3: The pre-dispersed slurry of the sheet-dot composite conductive-corrosion inhibitor prepared in S2 is mixed with the aqueous dispersion of phosphate-modified polysiloxane prepared in S1. γ-glycidyl etheroxypropyltrimethoxysilane is added and interfacial grafted onto the surfaces of sheet-like conductive mica powder and spherical antimony-doped tin oxide conductive titanium dioxide to obtain a mixed slurry. Separately, tridecafluorooctyltriethoxysilane and tetraethyl orthosilicate are mixed, and the pH is adjusted with glacial acetic acid while stirring for pre-hydrolysis to obtain a hydrolysate. The hydrolysate is mixed evenly with the mixed slurry, and fumed silica, polysiloxane defoamer, and polyether-modified polysiloxane leveling agent are added to generate fluorosilicone nanoparticles. After hydrolysis, the pH of the system is retested, and ammonia is used to adjust and maintain the pH value in the range of 5.8 to 6.
5. Subsequently, a polyurethane associative thickener is added to adjust the viscosity. The undispersed sheet-dot composite conductive-corrosion inhibitor agglomerates are removed by filtration to obtain component A. S4: Neutral alkoxysilane crosslinking agent is used as component B; component A and component B are mixed in a mass ratio and cured to obtain an antistatic and corrosion-resistant primer.
3. The preparation method of the conductive anti-corrosion primer material for air-raid shelter doors as described in claim 2, characterized in that, In step S1, the reaction under nitrogen protection requires heating to 80-100°C for 1-3 hours; after cooling, phosphoric acid is added dropwise, and the ring-opening reaction is carried out under heat preservation conditions, requiring cooling to 35-45°C and heat preservation for 25-35 minutes.
4. The preparation method of the conductive anti-corrosion primer material for air-raid shelter doors as described in claim 2, characterized in that, In step S1, the pH of the system is adjusted to 6.0-6.5; the conditions for high-speed shear emulsification are set to a rotation speed of 3000-5000 rpm and a shearing time of 10-20 minutes.
5. The preparation method of the conductive anti-corrosion primer material for air-raid shelter doors as described in claim 2, characterized in that, In step S2, the speed of the low-speed stirring is set to 400-600 rpm, and the stirring time is set to 8-12 minutes.
6. The preparation method of the conductive anti-corrosion primer material for air-raid shelter doors as described in claim 2, characterized in that, In step S2, increasing the stirring speed and performing medium-speed dispersion specifically means increasing the speed to 800~1200 rpm and performing medium-speed dispersion for 15~25 minutes; maintaining the speed and continuing medium-speed dispersion for 25~35 minutes.
7. The preparation method of the conductive anti-corrosion primer material for air-raid shelter doors as described in claim 2, characterized in that, In step S3, the stirring speed is set to 200~400 rpm; the pre-hydrolysis by adjusting the pH with glacial acetic acid and stirring specifically involves adjusting the pH value to the range of 4.5~5.0 and stirring at a temperature of 20~30℃ for 0.5~1.5 hours.
8. The preparation method of the conductive anti-corrosion primer material for air-raid shelter doors as described in claim 2, characterized in that, In step S4, the curing time is set to 8-12 minutes.
Citation Information
Patent Citations
Synthesis of siloxane-modified epoxy resin and preparation method of its waterborne anti-corrosion coating
CN107446116B
Water-based organic silicon anti-cracking anticorrosive coating and preparation method thereof
CN110628324A
Preparation method and application of condensed transparent silicone rubber
CN114409904A
